Hörensagenmarker, Deiktika und Zitierung des Niegesagten im Georgischen - Rostovtsev-Popiel , Alexander (Georgica, 2017)
The article discusses the so-called quotative particles (particles of reported speech) in Georgian, providing an analysis of their structure and their correlation with certain other areas and categories of linguistic structure. Attention is focused on the communicative status of these so-called quotative particles and the specific characteristics of quotation.